Інвестиційно-інноваційне забезпечення розвитку лісового сектору України - Дзюбенко, Олександр Миколайович (НУБіП України, 2021)
Дисертація на здобуття наукового ступеня доктора економічних наук зі спеціальності 08.00.06 «Економіка природокористування та охорони навколишнього середовища». Національний університет біоресурсів і природо-користування України. Київ, 2021. У дисертації розглянуто теоретико-методологічні основи інвестиційно-інноваційного забезпечення розвитку лісового сектору, зокрема розкрито суть інвестиційно-інноваційного забезпечення розвитку лісового сектору, виокремлено особливості інвестиційно-інноваційного забезпечення розвитку лісового господарства та проаналізовано зарубіжний досвід інвестиційно-інноваційного розвитку лісового сектору на предмет його імплементації у практику функціонування сировинного та переробного сегментів лісового сектору національного господарства України. Узагальнено теоретичні підходи та сформульовано авторське трактування поняття «інвестиційно-інноваційне забезпечення розвитку лісового сектору», яке розглядається як поєднання традиційних та інноваційних форм, методів, способів, інструментів та важелів фінансового забезпечення модернізації, реконструкції, оновлення та технічного переоснащення основного капіталу лісогосподарських підприємств та підприємств переробних ланок лісового сектору, а також впровадження сучасних продуктових інновацій та управлінських технологій у лісове господарство, переробку деревини, індустрію утилізації деревних відходів та у сферу залучення у господарський обіг несировинних корисностей лісу. У роботі розроблено авторський концепт класифікації інноваційних процесів у лісовому секторі, який виокремлює продуктові та процесні інновації у лісогосподарському та лісопереробному сегментах, які за відповідного інституціонального забезпечення дадуть можливість підвищити ефективність ведення лісового господарства та результативність використання Єлісосировини та несировинних корисностей у переробних та сервісних фазах лісопродуктового ланцюга. Сформовано інституціональне середовище інвестиційно-інноваційного забезпечення лісового сектору, що базується на інституціональному підґрунті, яке включає базові інститути лісогосподарювання, інститути інвестування та інституціональних інноваторів, що дозволяє диверсифікувати набір методів та способів господарського освоєння лісоресурсного потенціалу та підвищити ефективність залучення лісосировини та несировинних корисностей лісу у відтворювальний процес. Проведено оцінку бюджетно-інвестиційної спрямованості податкових платежів державних лісогосподарських підприємств, що надходять до Зведеного бюджету України та позабюджетних фондів, яка передбачає кластеризацію обласних управлінь лісового та мисливського господарства за наступними індикаторами: 1) рівень соціальної спрямованості (відношення суми єдиного соціального внеску до суми всіх податків, що сплачуються до Зведеного бюджету України, та єдиного соціального внеску); 2) рівень рентної спрямованості (відношення суми рентної плати, що надходить до публічних бюджетів, до загальної суми податків, які сплачуються до Зведеного бюджету України); рівень місцевої концентрації (відношення податків, що надійшли до місцевих бюджетів, до загальної суми податків, сплачених до публічних фінансових фондів). Сформовано механізм модернізації індустрії виробництва деревних енергоресурсів, який передбачає максимізацію використання паливно-енергетичного потенціалу лісового сектору, а саме: лісосічних відходів, відходів деревообробки, біоенергетичних культур та відходів сільсько-господарського виробництва, що використовуються у виробництві паливних енергетичних ресурсів на основі зв’язування з деревною сировиною.
Theses for the degree of Doctor of Economics in the specialty 08.00.06 «Economics of Nature Using and Environment Protection». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2021. The thesis considers theoretical and methodological bases of investment and innovative development of the forest sector, in particular the essence of investment and innovative development of the forest sector. The peculiarities of investment and innovative development of forestry are highlighted. The analysis of foreign experience of investment and innovative development of the forest sector for its implementation in practice of functioning of raw and processing segments of the forest sector of the national economy of Ukraine is performed. The theoretical approaches are summarized. The author's interpretation of the concept of «investment and innovative development of the forest sector» is provided. This interpretation is considered as a combination of traditional and innovative forms, methods, ways, instruments and tools of financial support modernization, reconstruction, upgrade and technical re-equipment of fixed capital from forest enterprises and enterprises of processing units of the forest sector and the implementation of modern product innovation and management technologies in forestry, timber processing, the wood waste recycling industry and the involvement of non-primary forest utilities in the economic turnover. The author's concept of classification of innovative processes in the forest sector has been developed, which identifies product and process innovations in the forestry and timber-processing segments, which are due to the appropriate institutional support (entry of forestry, woodworking, forest protection enterprises in statutory and non-statutory associations, the creation of international forestry associations of innovative orientation, the formation of advisory services to ensure the transfer of technologies to the raw materials and processing segment of the forest sector, the creation of associative associations based on the subjects of the processing sector of the forest sector) will make it possible to increase the efficiency of forest management and the effectiveness of the use of raw materials and non-raw materials in the processing and service phases of the forest product chain. Based on the study of existing author's approaches and theories of institutional support for forest management the institutional limitations of investment and innovative development of forestry are outlined. According to these limitations there are the following restrictions: 1) state ownership of forest and forestry assets; 2) overly centralized administration of forestry; 3) the lack of an institutional framework for vertical and horizontal integration of forest business entities for the production of product and process innovations; 4) the specification of forms, methods and sources of investment in forestry and forest protection projects has been narrowed; 5) a moratorium on the export of unprocessed wood. Based on the need of implementation in domestic practice of regulatory impact on the development of the resource sector the basic provisions of the Common agricultural policy of the European Union enhanced investment tools and innovative integration of agriculture and forestry. These tools are based on a set of assumptions that define the scope of interaction of subjects of agrarian entrepreneurship and permanent forest users that will allow you to obtain integrated ecological and economic effect, strengthen agricultural landscapes, reducing the scale of erosion and deflation processes, increasing the level of crop productivity, forming a reliable substrate for the absorption of mineral fertilizers, meliorants and plant protection products. Institutional environment of investment and innovation provide the forest sector based on institutional foundations, which includes basic forestry institutions, investment institutions and institutional innovators, allows you to diversify the set of methods and ways of economic development of forest resource capacity and to increase the efficiency of involvement of forest raw materials and raw materials of the forest in the reproduction process. This will allow increasing the share of added value in the forest sector, in the country’s GDP and ensuring an increase in the level of complexity of the use of raw wood and wood waste. A model of investment and innovation support for the modernization of woodworking production in the presence of a moratorium on the export of unprocessed wood, which provides for the implementation, along with the introduction of institutional restrictions on the export of round wood, of a set of state programs for the modernization and reconstruction of processing units of state and municipal forestry enterprises, as well as the activation of Bank lending projects for the introduction of additional capacities in the processing segment of the forest sector, in particular, the state reimburses commercial banks for part of the interest rates for credit resources provided to woodworking businesses for the purchase of high-tech equipment. The paper implements a strategic goal of investment and innovation support for the development of forestry at the regional level, which involves achieving the following goals: 1) expanding the scope of modernization, reconstruction and technical re-equipment of the active part of fixed assets of forestry enterprises; 2) forming the industry of growing planting material, creating modern breeding complexes, plantations and nurseries, purchasing and updating the park of forestry equipment for afforestation, construction and repair of anti-erosion hydraulic structures; 3) creation of a technical base to ensure continuous forest inventory, conduct soil isotopologues surveys, inventory of the forest fund and implement permanent monitoring of changes in breed and age structure of the forest fund; 4) formation of technical and technological base of conducting forest pathological examinations, carrying out of extermination works in the centers of pests and diseases, updating of the park of fire departmental protection, purchase of road construction equipment; 5) creation of modern systems of processing of logging waste and wood processing waste through the purchase of mobile and stationary chippers, the acquisition of lines for the production of pellets and wood briquettes, the implementation of innovative directions of the use of contaminated wood waste to obtain energy of conditioning quality. The assessment of the budget and investment orientation of tax payments of state forestry enterprises received from the Consolidated budget of Ukraine and extra-budgetary funds is performed. It provides clustering of regional departments of forestry and hunting on the following indicators: 1) the level of social orientation (the ratio of the amount of the unified social contribution to the amount of all taxes paid to the Consolidated budget of Ukraine, and the unified social contribution); 2) the level of rent orientation (the ratio of the amount of rent received in public budgets to the total amount of taxes paid to the Consolidated budget of Ukraine); the level of local concentration (the ratio of taxes received in local budgets to the total amount of taxes paid in public financial funds). A mechanism for modernizing the wood energy production industry has been formed, which provides for maximizing the use of the fuel and energy potential of the forest sector, namely: logging waste, wood processing waste, consumed wood, bioenergy crops and agricultural waste used in the production of fuel and energy resources based on binding with wood raw materials. It is established that the activation of the processes of effective use of the fuel and energy potential of the forest sector should be based on the system of institutional support for innovative and technological modernization of the wood energy products industry, which provides for the expansion of various types of public and private partnership, the creation of municipal enterprises with the participation of regional and basic level territorial communities, the formation of associations of associative, cluster and cooperative types, and the institutionalization of forms of direct and indirect state financial support. It is proved that the institutional support for innovative and technological modernization of the wood energy products industry should provide for the creation of prerequisites for the introduction of innovative forms and methods of increasing and using the fuel and energy potential of the forest sector. It is established that such innovative forms and methods should be: reengineering the use of logging waste and other components of forest biomass; the use of franchising forms of establishing the production of wood energy resources; application of outsourcing methods in harvesting, processing and storage of wood biomass in the energy sector; transfer of modern technologies for processing wood waste, used wood and bioenergy crops; production and technical cooperation of permanent forest users, woodworking businesses and households.
Keywords: інвестиційно-інноваційне забезпечення; лісовий сектор; інституціональне середовище; еколого-економічний ефект; лісогосподарське підприємництво; переробний сегмент; деревні енергетичні продукти; постійні лісокористувачі; investment and innovation support; forest sector; institutional environment